Potential Role of Cannabidiol on Sports Recovery: A Narrative Review - Rojas-Valverde, Daniel (Frontiers in Physiology, 2021)
The use of cannabidiol (CBD) among athletes is becoming extensive and frequent. This could be due to the elimination of CBD from the list of prohibited substances by federations and international institutions of sport. The legalization and resulting production, and commercialization of CBD, could increase its intake in sports professionals. This commercialization of cannabinoids has fueled a race to study their properties, benefits, and risks for health and performance in athletes. Although there is evidence that suggests some beneficial properties such as anxiolytics, antidepressants, anti-inflammatory, and antioxidants among others, the evidence presented so far is neither clear nor conclusive. There are significant gaps in knowledge of the physiological pathways that explain the role of CBD in sports performance. This mini-review examines evidence suggesting that CBD has the potential to be used as a part of the strategies to recover from fatigue and muscle damage related to physical and cognitive exertion in sports.